Murder at Donwell Abbey - Kelly, Vanessa (Kelly, Vanessa. Emma Knightley mystery, 2025)
"Emma's spirits are elevated after she and husband George Knightley host a joyful holiday celebration at the Hartfield estate. But it's instantly a bitter January when her father makes an unexpected announcement--he and Miss Hetty Bates have decided to marry. Not only must Emma relinquish her role as mistress of the household, but also accept the reality that the excitable Miss Bates will become her stepmother... More unwanted news arrives during an extravagant betrothal ball at Donwell Abbey, the grand Knightley estate where Emma and George will soon permanently reside. Nearly every villager in Highbury revels in the dazzling affair--except Emma's hardworking lady's maid, Prudence Parr. To Emma's horror, Prudence is found dead, sprawled across the stones of the library terrace... The woman's tragic fall is quickly ruled a terrible accident and whispers circulate around personal troubles leading up to her untimely demise. But Emma's instincts tell her that something far more sinister is at play. Now, Highbury's matchmaker-turned-sleuth vows to outwit a cunning criminal before an innocent man loses his freedom--or Donwell Abbey plungesinto a darker mystery..."--